Answer:
y = -4x+7 is the equation simplified and answer choice A is the right answer.
Explanation:
Your equation: y - 6 = -4(x+1)
Your Objective: You need to simplify the original equation and find another equation that is equivalent to the original equation.
Let's focus on the -4(x+1) side first.
This needs to have the distributive property applied.
Take -4 and multiply it by x and 1.
You should have -4x+1
Your equation now:
y - 6 = -4x+1
We want y to be by itself.
So add 6 to both sides.
y = -4x+1+6
Use PEMDAS
y = -4x+7
The first answer choice "A" is correct.